Intake of antioxidant vitamins and risk of Parkinson's disease. Issue 12 (27th October 2016) - Hughes, Katherine C.; Gao, Xiang; Kim, Iris Y.; Rimm, Eric B.; Wang, Molin; Weisskopf, Marc G.; Schwarzschild, Michael A.; Ascherio, Alberto
ABSTRACT: Introduction: Oxidative stress is proposed to be one of the potential mechanisms leading to neurodegeneration in Parkinson's disease. However, previous epidemiologic studies investigating associations between antioxidant vitamins, such as vitamins E and C and carotenoids, and PD risk have produced inconsistent results. Objective: The objective of this work was to prospectively examine associations between intakes of antioxidant vitamins, including vitamins E and C and carotenoids, and PD risk. Methods: Cases were identified in two large cohorts: the Nurses' Health Study and the Health Professionals Follow‐up Study. Cohort members completed semiquantitative food frequency questionnaires every 4 years. Results: A total of 1036 PD cases were identified. Dietary intakes of vitamin E and carotenoids were not associated with PD risk; the multivariable‐adjusted relative risk comparing extreme intake quintiles were 0.93 (95% confidence interval: 0.75–1.14) and 0.97 (95% confidence interval: 0.69–1.37), respectively. Dietary vitamin C intake was significantly associated with reduced PD risk (relative risk: 0.81; 95% confidence interval: 0.65–1.01; p trend, 0.01); however, this result was not significant in a 4‐year lag analysis. For vitamins E and C, intake from foods and supplements combined were also unrelated to PD risk. Conclusions: Our results do not support the hypothesis that intake of antioxidant vitamins reduces the risk of PD. © 2016 International Parkinson and Movement Disorder Society